Штучний інтелект: напрямки розробок та соціальні наслідки - Столяренко, О. А. (ХНУРЕ, 2023)
Artificial Intelligence it is one of the fastest growing technology industries in the modern world. Discussed two major classifications of AI development based on capabilities and functionality. Knowledge of these directions helps to pay attention and direct efforts to the development of those AI systems that are most promising for solving specific tasks. Positive and negative social consequences that can be caused by the introduction of artificial intelligence are considered.